Climate variability and extremes in the Okavango River Basin, southern Africa - Moses, Oliver (Department of Oceanography, 2023)
The Okavango River Basin (ORB) located in southern Africa is a region of highly sensitive and biodiverse ecosystems. It spans Angola, Namibia and Botswana, with the world-famous Okavango Delta located in the latter country. The ecosystems depend on the highly seasonal ORB streamflow, which is also the major source of freshwater for the rural population, most of whom depend on subsistence farming. Climate variability and extremes such as droughts, hot days and extreme rainfall events are not well understood over this region. Also, the relationship between climate and other aspects like vegetation and river discharge are not well understood. To contribute to a better understanding of this relationship, the thesis investigated relationships between rainfall, temperature, Normalized Difference Vegetation Index (NDVI) and river discharge, and their interannual variability and trends. It was found that at monthly and seasonal time scales, NDVI spatial patterns are closely related to those of rainfall than temperature. The NDVI-rainfall and NDVI-temperature relationships differ north of 18.9°S where rainfall is higher than to its south. Correlations between NDVI and rainfall show lags of 1-2-months. Large areas across the region show significant warming trends in all seasons but mainly in October-December (OND), as well as wetting mainly in the north. The warming trend may imply more evaporation and desiccation which may exacerbate extreme event impacts such as severe droughts. Interannual variability of rainfall, NDVI and temperature is pronounced with significant correlations with El Niño-Southern Oscillation (ENSO), the subtropical Indian Ocean Dipole (SIOD) and the Botswana High for rainfall and temperature, and for NDVI with ENSO. The temperature (rainfall) correlations with ENSO and the Botswana were positive (negative), with the SIOD they were negative (positive), and the NDVI-ENSO correlations were negative. On longer time scales, the wet 2006-2013 period was analysed relative to much drier 1999-2005 epoch for OND. The 2006-2013 wetter conditions appear linked to La Niña Modoki conditions, regional circulation differences and warmer sea surface temperature near Angola. Extreme rainfall events over the ORB were analysed. The analysis was performed within a larger region in western central southern Africa (WCSA), given that many rainfall events extend beyond river basin boundaries. Focus was placed on extreme rainfall events accumulated over 1-day (DP1) and 3-days (DP3), during the main rainy season, January-April (JFMA). Due to data sparsity, the Climate Hazards Group Infrared Precipitation with Station data (CHIRPS) were used to identify these events. It was found that contributions of DP1 and DP3 events to JFMA rainfall totals are, on average, ~10% and ~17%, respectively, but in some years their contributions exceed 30%. Most of the events result from tropical-extratropical cloud bands, with tropical lows being also important. Interannual variability in extreme events is substantial and appears linked to ENSO and the Botswana High. Although ENSO influences the extreme events and rainfall totals more generally over southern Africa, by far the neutral JFMA 2017 season experienced the wettest conditions over the world-famous Okavango Delta region. Factors that contributed to these heavy rains included a deeper Angola Low, weaker mid-level Botswana High and anomalous westerly moisture fluxes from the tropical southeast Atlantic during January – early March. The second most intense rainfall event occurred on April 22nd, resulting from a cut-off low. DP1 frequencies show significant increasing trends, and similarly, rain-days and rain totals over many areas. These trends have important implications for agricultural and water management as well as wildlife conservation in the ORB. To contribute to a better understanding of drought over the ORB region, the thesis analysed various drought metrics. These include a Cumulative Drought Intensity (CDI) index, based on the product of maximum dry spell duration and maximum temperature anomaly, and the Standardised Precipitation-Evapotranspiration Index (SPEI). Strong horizontal gradients in frequencies of dry spells and hot days were found to shift south over the ORB from August to November as the tropical rain-belt shifts increasingly south of the equator, the Congo Air Boundary declines and the Botswana High strengthens and shifts south-westwards. By December, the tropical gradient in dry spell frequencies is unnoticeable while that across the Limpopo River and southern ORB region, where the Botswana High is centred, stands out. On seasonal time scales, October-November 2013-2021 is particularly hot and dry over the Okavango Delta region. The thesis provided evidence that this hot and dry epoch is related to a stronger and southward shifted Botswana High and reduced low-level moisture convergence. On interannual time scales, there were strong relationships with the Botswana High, and to lesser extent ENSO. A strong drying-warming trend was found in the early summer, linked to a significant strengthening of the Botswana High. These trends, in conjunction with the Coupled Model Intercomparison Project Phase 6 (CMIP6) projected early summer drying over southern Africa found in the literature, may impact severely on the sensitive ecosystems of the ORB, and on water availability as well as subsistence farming in the region.